О систематическом положении вяхиря (Aves, Columbiformes) - Воинственский, M.А. (Вестник зоологии, 1993)
An analysis of morphological. ecological and ethological characters show the wood pigeon to be more closely related to doves than to pigeons, and represent a distinct genus. Palumba gen. n. is es’.ablished for Columba palumbus L.